Integration of Monetary Systems in Poland after World War I and World War II - Landau, Zbigniew (Studia Historiae Oeconomicae, 2006)
A well-functioning monetary system has always been an essential element of a normally functioning economy. When after 1918 and in 1944-1945 the economy of Poland was disorganized both as a result of war damage and in consequence of the policies of occupants' administrations, restoration of an efficient monetary system turned out to be one of the most urgent tasks of the state. In Poland, the situation after the world wars was particularly difficult, since the occupying powers consciously had developed monetary systems which suited their war effort, not the future goals of the Polish state.